Can Donor Coordination Solve the Aid Proliferation Problem? - Rahman, Aminur; Sawada, Yasuyuki (2012)
The paper augments Holmstrom s (1982) team production model in the context of aid effectiveness. The analysis shows how donor proliferation leads to inefficient supply of aid in the recipient country because of the free-riding problem faced by the donors. The empirical findings support the theoretical prediction with regard to donor proliferation. However, this raises the question whether the current efforts in the international aid community with regard to donor coordination can in fact solve the aid proliferation problem.